Safety and efficacy of hyaluronic acid injectable filler in the treatment of nasolabial fold wrinkle: a randomized, double-blind, self-controlled clinical trial - Xing-Zhou Li; Chi-Fu Chiang; Yung-Hsiang Lin; Tim-Mo Chen; Chih-Hsing Wang; Yuan-Sheng Tzeng; Hai-Yan Cui (Taylor & Francis Group, 2023)
Introduction The injectable skin fillers available for soft tissue augmentation are constantly growing, providing esthetic surgeons with more options in the treatment of scars, lines, and wrinkles. Hyaluronic acid (HA)-derived injectable fillers are ideal to reduce the appearance of nasolabial folding. This study investigated the efficacy and safety of the commercially available HA filler from Maxigen Biotech Inc. (MBI-FD) in the treatment of nasolabial folds (NLFs). Methods We analyzed 1,4-butanediol diglycidyl ether (BDDE) residues and injection force test and observed the protein content in MBI-FD, and then was cultured in fibroblast L929 cells and examined for cytotoxicity. Finally, 95 healthy participants underwent dermal filler injection therapy to evaluate the efficacy and safety for 24 and 52 weeks, respectively. Results BDDE residues in MBI-FD was <0.125 µg/mL. MBI-FD was fitted using 27- and 30-G injection needles with an average pushing force of 14.30 ± 2.07 and 36.43 ± 3.11 N, respectively. Sodium hyaluronate protein in MBI-FD was 7.19 µg/g. The cell viabilities of 1× and 0.5× MBI-FD were 83.25% ± 3.58% and 82.23% ± 1.85%, respectively, indicating MBI-FD had no cytotoxicity, and decreased NLF wrinkles with no serious adverse events. Conclusion MBI-FD is an effective filler for tissue augmentation of the NLFs and may be a suitable candidate as an injectable dermal filler for tissue augmentation in humans in the future.